Feasibility of Virtual Assessment of Physical Frailty in Solid Organ Transplant Recipients – A Single Centre, Observational Study - Manoela de Paula Ferreira; Noori Chowdhury; Lisa Wickerson; Heather Ross; Nazia Selzner; S. Joseph Kim; Lianne G. Singer; Sunita Mathur (International Journal of Telerehabilitation)
Objectives: To describe the feasibility of virtual assessments of physical frailty in solid organ transplant (SOT) recipients using a modified Fried Frailty Index (mFFI) and Short Physical Performance Battery (SPPB), and to describe the prevalence of frailty 12-months post-transplant using virtual assessment. Methods: Virtual assessments were performed using an e-questionnaire and a video-call for functional tests. Feasibility variables included: internet quality, video-call duration, presence of a companion, and adverse events. Results: 34 SOT recipients, median age 62 (46-67), 76% lung recipients, 47% female, were included. The video-call had a median duration of 12 minutes (10-15 min), without adverse events. A companion was present in 23 (68%) video-call assessments. Fifteen SOT recipients (44%) were classified as pre-frail by the mFFI, and none were frail. Three participants (8.8%) were classified as frail using the SPPB. Conclusion: Virtual frailty assessments can be used as an alternative to in-person assessments in SOT recipients.